Regenerative therapy in young permanent tooth: Case report (Research, Society and Development, 2023)
Pulp necrosis in immature permanent teeth represents a challenge for clinical management. The dentin wall in immature teeth is thin and the root is short, leading to an unfavorable long-term prognosis due to the risk of root fracture. Regenerative endodontic procedures have been shown to be effective and improve the prognosis of the compromised immature tooth by re-establishing functional pulp tissue that promotes continued root development and immune competence. The objective of the study was to report a case of a young permanent molar, diagnosed with necrosis and incomplete rhizogenesis. A female patient, 08 years old, attended the clinic of the specialization course in Endodontics, Faculty of Dentistry São Leopoldo Mandic, Belo Horizonte Unit. Regenerative therapy was proposed, which involved the following steps: anesthesia, opening, odontometry, minimal instrumentation, disinfection with 2% chlorhexidine gel, irrigation with saline solution, intracanal medication with calcium hydroxide paste, induction of bleeding to form a blood clot, cervical sealing with mineral trioxide aggregate and composite resin. The patient remained symptom-free up to 5 months after treatment. However, radiographically, an increase in the periapical radiolucent area was noted, so it was decided to carry out the conventional endodontic treatment. Regenerative therapy can be an alternative to apexification in immature teeth in cases of irreversible pulpitis and pulp necrosis associated or not with a periapicalesionson. It is a simple treatment with advantageous results as it promotes an increase in the length and thickness of the dentin wall and apical closure as seen in the case described in this work.